2019
DOI: 10.1080/09712119.2019.1624553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microwave heating on physicochemical properties, microstructure and volatile profiles of yak meat

Abstract: The effects of microwave cooking on the changes of physical properties, protein denaturation, microstructure and volatiles of yak meat were investigated. Various microwave power settings were used for cooking the yak longissimus meats, and SDS-PAGE, cooking loss, colour difference, shear force, microstructure and volatile flavour compounds of longissimus muscle were evaluated. Cooking losses (37.03-45.92%) and shear forces (257.20-315.57 N) in microwave heated meats were higher and lower, respectively, than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…For secondary oxidation products, determination of content of thiobarbituric acid reactive substances (TBARS) is commonly used in addition to determination anisidine value. The fatty acid composition and other related compounds can also be used to determine changes in lipids during storage and processing but is usually not sensitive enough to detect small changes [4,118].…”
Section: Traditional Analysis Methodsmentioning
confidence: 99%
“…For secondary oxidation products, determination of content of thiobarbituric acid reactive substances (TBARS) is commonly used in addition to determination anisidine value. The fatty acid composition and other related compounds can also be used to determine changes in lipids during storage and processing but is usually not sensitive enough to detect small changes [4,118].…”
Section: Traditional Analysis Methodsmentioning
confidence: 99%
“…The main obstacles include nonhomogeneous heating and high cost for the equipment, although various solutions have been proposed recently to overcome some of these limitations (Chizoba Ekezie et al 2017). Numerous studies have reported the superiority of microwave heating compared to traditional water bath or oven (Calabrò and Magazù 2012;Han et al 2019b;Li et al 2019;Taşkıran et al 2020). More details about these studies will be given in section 3.…”
Section: Microwave and Radio Frequency Heatingmentioning
confidence: 99%
“…Apart from colour and texture, meat flavour (taste and odour) is also an important component of the sensory quality. Flavour compounds in meat are usually formed by thermal degradation of sugar, proteins, fat, and fatty acids (Chen et al 2020;Li et al 2019;Xiong et al 2014). Food flavour and volatile compounds responsible for flavour are often determined by chromatographic techniques.…”
Section: Sensory and Microbiological Analysismentioning
confidence: 99%
“…Many researchers study Yak meat quality, and they are focused on the effect of the breed of beef, feeding time, gender, trophic levels, and feed additives on tenderness [8,9] . Postmortem tender process, color stability and water holding capacity of yak meat were also studied [9,10] . Meat processing and meat quality of yak in different ages during postmortem aging were also investigated [9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…Postmortem tender process, color stability and water holding capacity of yak meat were also studied [9,10] . Meat processing and meat quality of yak in different ages during postmortem aging were also investigated [9,10] . However reports about the difference of yak meat tenderness and the mechanism are very few.…”
Section: Introductionmentioning
confidence: 99%